Factors influencing the demand for psychological counseling among senior students at Van Lang University - Le , Văn Lộc; Ton, Nguyễn Trọng Hiền (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study explores the factors influencing the demand for psychological counseling among senior students at Van Lang University. Using SPSS for data analysis, five initial hypotheses were tested and accepted. The results indicate that academic pressure, interpersonal communication, personal development challenges, awareness of the benefits of counseling, and university culture all show statistically significant and positive correlations with students’ psychological counseling needs. Regression analysis identified personal development difficulties and academic pressure as the most influential factors. This reflects the practical needs of senior students in seeking psychological support and career guidance as they prepare for the post-graduation phase. The study also compares its findings with AI-generated citation data from Scite.ai, thereby reinforcing the academic relevance of the key research variables